PENGARUH UKURAN PERUSAHAAN, CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN ENERGY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2022) - Anggraeni, Nur Trilap; Fitriyana, Fina (Jurnal Nusa Akuntansi, 2024)
This research aims to determine the influence of company size, Capital Intensity, and Inventory Intensity on tax aggressiveness. The population of this research is Energy companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The number of samples obtained using purposive sampling technique was 13 companies with observations for 6 years. The research method used is a quantitative method using secondary data. Meanwhile, the data collection technique used is the documentary collection technique, namely the use of data originating from existing documents. This documentary method is carried out by collecting annual reports, financial reports and other necessary data. The results of this research show that company size, Capital Intensity, and Inventory Intensity simultaneously influence tax aggressiveness, and partially company size, Capital Intensity, and InventoryIntensity do not influence tax aggressiveness.